2015
DOI: 10.1016/j.meatsci.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of blood loss during the Halal slaughter of lambs following Traditional Religious Slaughter without stunning, Electric Head-Only Stunning and Post-Cut Electric Head-Only Stunning

Abstract: Blood lost at exsanguination during the Halal slaughter of lambs was compared between the slaughter methods of Traditional Religious Slaughter without stunning (TRS), Electric Head-Only Stunning (EHOS) and Post-Cut Electric Head-Only Stunning (PCEHOS). Two protocols were examined, Experimental (80 lambs) and Commercial (360 lambs), assessing varying periods of animal orientation during the 4 min bleeding process (upright orientation before vertical hanging). Live-weight, blood weight (Experimental only), carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 23 publications
1
47
0
1
Order By: Relevance
“…Our findings also revealed that the majority of UK scholars (95%) would regard meat from stunned animals as Halal on condition that it is proven to be reversible, however, 25% of those who would regard stunned meat as Halal did not think stunning should be encouraged during Halal slaughter because they believe the practice impedes bleeding out, leads to poor meat quality and that it is an inhumane and cruel practice. Research has however demonstrated that the stunning of animals before slaughter has no adverse effects on blood loss (Anil et al, 2004, 2006, Khalid, Knowles & Wotton, 2015, meat quality (Önenç and Kaya, 2004) and the humaneness of stunning has been objectively measured with EEG (Newhook and Blackmore, 1982). A further 7% did not think stunning is suitable for Halal poultry, according to the scholars, this is because of a high risk of birds dying due to their size.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also revealed that the majority of UK scholars (95%) would regard meat from stunned animals as Halal on condition that it is proven to be reversible, however, 25% of those who would regard stunned meat as Halal did not think stunning should be encouraged during Halal slaughter because they believe the practice impedes bleeding out, leads to poor meat quality and that it is an inhumane and cruel practice. Research has however demonstrated that the stunning of animals before slaughter has no adverse effects on blood loss (Anil et al, 2004, 2006, Khalid, Knowles & Wotton, 2015, meat quality (Önenç and Kaya, 2004) and the humaneness of stunning has been objectively measured with EEG (Newhook and Blackmore, 1982). A further 7% did not think stunning is suitable for Halal poultry, according to the scholars, this is because of a high risk of birds dying due to their size.…”
Section: Discussionmentioning
confidence: 99%
“…Others are of the opinion that the stunning of animals prior to slaughter results in the retention of more blood in the carcass in comparison with those slaughtered without stunning. However, repeated research has demonstrated that there is no difference in animals that are slaughtered either with or without pre-slaughter stunning in terms of the total blood lost at exsanguination (Khalid et al 2015;Anil et al 2006;Gomes Neves et al 2009). In addition, some methods of stunning e.g.…”
Section: What Is Halalmentioning
confidence: 99%
“…The majority of the concerns raised have been addressed through research. It has been demonstrated that the total blood loss at slaughter is not significantly different whether animals are pre-stunned, post-stunned or slaughtered without stunning (Anil et al, 2004, 2006, Gomes Neves et al, 2009, Khalid et al, 2015. On the issue of product quality, Önenç and Kaya (2004) showed that percussive captive bolt stunning of young bulls offered improved meat quality characteristics in comparison with animals slaughtered using head-only electrical stunning or those slaughtered without stunning.…”
Section: The Halal Stunning Debatementioning
confidence: 99%
“…The widespread use of irreversible stunning for Halal slaughter is of grave concern to Halal consumers. Reversible headonly electrical stunning may resolve the issue of slaughtering dead animals for Muslim consumption since there is some level of assurance that unconsciousness is induced through temporary disruption of brain function and there is no evidence to suggest that head-only electrical stunning induces ventricular fibrillation or other significant dysrhythmias that result in death before slaughter (Khalid et al, 2015).…”
Section: The Presence Of a Beating Heart After Stunningmentioning
confidence: 99%